Вивчення ливарних властивостей фторфлогопітових розплавів - Малявін, А.Г.; Кузьменко, О.А. (Physico-technological Institute of Metals and Alloys, 2023)
The article presents the results of studying the viscosity and fluidity of fluoroflogopite melts of various chemical composition. For convenience of calculations, the chemical composition of the melt is expressed in terms of a generalized indicator – aluminosilicate module, which is the ratio of the ionic amount of grid-forming silicon cations Si4+ and aluminum Al3+. The viscosity of fluoroflogopite melts in the range of cooking temperatures (1450–1500 °C) is 0.25–0.53 n·s/m2. The low viscosity of fluoroflogopite melts during the melting of the mixture and the preparation of melts contributes to the accelerated flow of solid-phase reactions and to obtain a homogeneous homogeneous melt, and when pouring it into casting molds, to obtain high-quality shaped stone castings. The main influence on viscosity is exerted by temperature and, to a lesser extent, aluminosilicate module. The viscosity of fluoroflogopite melts increases with decreasing temperature exponentially until the process of crystallization and solidification begins. The low viscosity of fluoroflogopite melts is obviously a consequence of the depolymerizing effect of modifier cations (K1+, Mg2+, Ca2+) and fluorine anions (F1-) on the structural units of the melt, the total amount of which significantly exceeds the number of glass-forming cations (Si4+, Al3+). The study of fluidity showed that it linearly increases with increasing temperature and a decrease in aluminosilicate module. The equation of regression of the dependence of fluidity on temperature and aluminosilicate module is obtained. When pouring fluoroflogopite melt into casting molds in the temperature range of 1400–1450 °C, the fluidity is 360–480 mm. Such fluidity ensures a good filling of the molds with a melt and the production of shaped stone castings of a wide range.